2007
DOI: 10.1007/s00449-006-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of inulinase by solid-state fermentation: effect of process parameters on production and preliminary characterization of enzyme preparations

Abstract: This work was aimed at producing inulinase by solid-state fermentation of sugarcane bagasse, using factorial design to identify the effect of corn steep liquor (CSL) and soybean bran concentration, particle size of bagasse and size of inoculum. Maximum inulinase activity achieved was 250 U per g of dry substrate (gds) at 20% (w/w) of CSL, 5% (w/w) of soybean bran, 1 x 10(10) cells mL(-1) and particle size of bagasse in the range 9/32 mesh. The use of soybean bran decreased the time to reach maximum activity fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
5
43
0
4
Order By: Relevance
“…These values are in agreement with previous work carried out by Mazutti et al (2007) and Treichel et al (2009), who evaluated the free enzyme in 0.1M sodium acetate buffer at pH 4.8. Mazutti et al (2007) found 17.2 U.mL -1 for v max and 7.1 mM for k m , while Treichel et al (2009) reported 10.7 U.mL -1 and 13.0 mM for v max and k m , respectively.…”
Section: Effect Of Ph On Inulinase Stabilitysupporting
confidence: 93%
See 4 more Smart Citations
“…These values are in agreement with previous work carried out by Mazutti et al (2007) and Treichel et al (2009), who evaluated the free enzyme in 0.1M sodium acetate buffer at pH 4.8. Mazutti et al (2007) found 17.2 U.mL -1 for v max and 7.1 mM for k m , while Treichel et al (2009) reported 10.7 U.mL -1 and 13.0 mM for v max and k m , respectively.…”
Section: Effect Of Ph On Inulinase Stabilitysupporting
confidence: 93%
“…Since Ed values represents the energy necessary to start the inactivation reaction and this value was lower for the immobilized enzyme than that for the free enzyme, one can conclude that the immobilized enzyme was less stable than the free enzyme when using this immobilization method (Santos et al, 2007). These results are similar to those reported by Mazutti et al (2007) (343.9 kJ.mol -1 ) and lower than those of Treichel et al (2009) (527 kJ.mol -1 ) for free inulinase.…”
Section: Effect Of Temperature On Inulinase Stabilitysupporting
confidence: 80%
See 3 more Smart Citations